PENENTUAN JUMLAH PRODUKSI MENGGUNAKAN MODEL FUZZY MULTI OBJECTIVE LINEAR PROGRAMMING PADA INDUSTRI PANGAN (Studi Kasus Pada Industri Roti PT NIC) - Iveline Anne Marie; Eriyatno Eriyatno; Yandra Arkeman; Dadan Umar Daihani (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
Production Planning and Inventory Control (PPIC) activities in the food industry requires a reliable decision model to support the effectiveness and efficiency of PPIC function. Master Production Scheduling / MPS is one of the PPIC decision model that aims to get the number of items that must be produced by the company to meet consumer demand based on its production capacity. This research had been done in the food industry with a case study on PT NIC bread industry, using Fuzzy Multi Objective Linear Programming Model as a decision model to determine the amount of production.This model is an optimization model that was developed by utilizing the modified S-curve membership function for Fuzzy Linear Programming problems with the aim of minimizing costs and maximizing production utilization. This model is reliable enough to improve the functioning of PPIC in the food industry.